Konferencja „Dziecko w rodzinie i społeczeństwie” - Pieczyska 24 - 26.06.2002 - Kabacińska, Katarzyna (Biuletyn Historii Wychowania, 2002)
Konferencja „Dziecko w rodzinie i społeczeństwie” - Pieczyska 24 - 26.06.2002